Filozofia, religia i poezja w poszukiwaniu nieskończoności - Szulakiewicz, Marek (Humaniora. Czasopismo Internetowe, 2023)
Man in contemporary culture thinks about the finite by starting from the finite (M. Foucault). The loss of reference to the infinite is not only the dominance of the naturalistic worldview, which rejects the possibility of any transcendent dimensions of the world. It is also a profound change in the areas of life that form the basis of our existence. They all tune in, so to speak, to the „man without infinity.” Historically, it has been common for us to move away from the present towards “more” and “different.” The desire for such infinity was also at the heart of cultural work. The lecture seeks to answer two questions: what happens when we lose the ability to consider infinity as a condition of the possibility of our experience? And: do philosophy, religion, and poetry still liberate us from the danger of finitude?